PERAN PENDIDIKAN AGAMA ISLAM DALAM MENANGGULANGI KRISIS KARAKTER PADA MURID SMA MUHAMMADIYAH 2 BOJA - Puji Astutik; Mukhammad Anieg (As-Sulthan Journal of Education, 2025)
The character crisis among teenagers, especially among high school students, is a complex challenge in the current educational context. Signs of this problem can be seen from an increase in negative attitudes, including decreased ethics in communication, reduced respect for teachers, and low attention to the social environment. At SMA Muhammadiyah 2 Boja, this issue is also felt, especially due to the influence of the external environment, developments in digital technology, and limited comprehensive moral development. This research aims to examine the contribution of Islamic Religious Education (PAI) in overcoming the character crisis problem and forming student behavior with good character. The research method used is descriptive qualitative with a literature review, observation and interview approach. The results of this research show that PAI has a significant impact in shaping students' character through comprehensive teaching methods, religious activity habits, and examples from teachers. Routine activities such as morning tadarus, midday prayers, memorizing verses and hadith, as well as implementing daily adab are effective means of instilling strong religious values. Apart from that, the values ​​of cooperation, togetherness and the spirit of doing good with sincere intentions are promoted in every activity, both formal and informal.